Vertisol surface drainage and effects on soil and nutrient conservation, excess water disposal and wheat growth at Debre Zeit - Astatke, A.; Jutzi, S.C.; Grunder, M. (Institute of Agricultural Research, 1989)
Gives results of the 1987 main rainy season results of the trials conducted to determine the effects of vertisol surface drainage on soil and nutrient conservation, excess water disposal and wheat growth at the Debre Zeit ILCA station and at Hidi.